Practice Patterns of Radiotherapy in Endometrial Cancer Among Member Groups of the Gynecologic Cancer Intergroup. Issue 3 (1st March 2009) - Small, William; Du Bois, Andreas; Bhatnagar, Saurabha; Reed, Nick; Pignata, Sandro; Potter, Richard; Randall, Marcus; Mirza, Monsoor; Trimble, Edward; Gaffney, David
Abstract : Purpose: To describe radiotherapeutic practice of the treatment of endometrial cancer in members of the Gynecologic Cancer Intergroup (GCIG). Methods: A survey was developed and distributed to the members of the GCIG. The GCIG is a global association of cooperative groups involved in the research and treatment of gynecologic neoplasms. Results: Thirty-four surveys were returned from 13 different cooperative groups. For the treatment of endometrial cancer after hysterectomy, mean (SD) pelvic dose was 47.37 (2.32) Gy. The upper border of the pelvic field was L4/5 in 14 respondents, L5/S1 in 13 respondents, and not specified in 6 surveys. When vaginal brachytherapy (VBT) was used in conjunction with external beam radiotherapy, most groups used high dose rate versus low dose rate on 24 versus 5 respondents, respectively. Twenty-eight of the 34 respondents performed computed tomographic simulation. Intensity-modulated radiotherapy was used routinely in 3 of the 34 respondents. For a para-aortic field, the upper border was, most commonly, at the T12-L1 interspace (17 of the 28 respondents), and the mean (SD) dose was 46.15 (2.18) Gy. For VBT alone after hysterectomy, 23 groups performed high-dose-rate brachytherapy (27.57 [10.13] Gy in a mean of 4.3 insertions), and 5 groups used low-dose-rate brachytherapy (41.45 [17.5] Gy). Nineteen of the 28 respondents measured the doses to the bladder and the rectum when performing VBT. For brachytherapy, there was no uniformity in the fraction of the vagina treated or the doses and schedules used. Conclusions: Radiotherapy practices among member groups of the GCIG are similar in doses and dose per fraction with external beam. There is a moderate discrepancy in the brachytherapy practice after hysterectomy. There are no serious impediments to intergroup participation in radiation oncology practices among GCIG members with the use of external beam.